Applicability of the Yoyo intermittent recovery test level 2 for the assessment of repeated high-intensity running capability in youth professional soccer players - Mukherjee, S.; Chia, Y. H. M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In soccer, the higher the level of performance, the greater is the amount of high-intensity running performed by the players. The YoYo Intermittent Recovery Test (YoYo IRT L2) is a reliable and valid measure for assessing repeated high-intensity running capability in elite adult soccer players. However, the applicability of this test in youth professional soccer players is apparently not yet evaluated. The aim of the study was to evaluate the applicability of the YoYo IRT L2 for the assessment of repeated high-intensity running in youth professional soccer players during different phases of a complete soccer season. Methods Twenty youth professional soccer players (mean ± SD: age, 17.5 ± 0.3 years; stature, 1.73 ± 0.04 m; body mass, 67.2 ± 7.5 kg) participated in the study. The participants completed a laboratory-based test of intermittent high-intensity on a motorized treadmill, the YoYo IRT L2 as a field-based test of intermittent high-intensity running, a repeated sprint ability (RSA) test on a non-motorised treadmill (6 × 6 s with 24 s recovery) and a field-based RSA test (8 × 20 m with 15 s active recovery) on three occasions (pre-season, early in-season and end mid-season) during the soccer season. The study also determined the work intensity during match play using heart rate (HR) monitoring for two matches during each phase of the competition season. Results Significant correlations (p<0.05) were observed between the laboratory test of intermittent high-intensity running (Range; r = 0.53- 0.85) and performance in the YoYo IRT L2 (Range; r = 0.55- 0.81) with the amount of high-intensity work performed during match play (HR > 90% of HRmax for % of total playing time). Non-significant correlations were found between the tests of RSA and match play work intensity. Results also showed that the performance in the YoYoIRT L2 (distance covered, mean; 818, 950*, 1032 m; * significant change from the previous phase) and the amount of high-intensity work performed during match play (57.5, 69.5*, 58* %) changed through the soccer season Discussion The development and assessment of repeated high-intensity running capability should be of important concern for soccer scientists and coaches. The results strongly supported the validity of intermittent high-intensity running tests for the evaluation of match performance in youth professional soccer players in terms of high-intensity work performed during matches. However, the YoYo IRT L2 being field-based, simple to conduct, with the option of simultaneous multiple player testing and therefore is time economical. The YoYo IRT L2 has an advantage over the laboratory-based test that requires specialized facilities and manpower. Furthermore, the results showed that the YoYo IRT L2 was sensitive to the changes in the repeated high-intensity running capability through the playing season in youth professional soccer players.